Resistance mechanism of Limnocharis flava (L.) Buchenau to acetohydroxy acid synthase inhibitors - Zakaria, Norazua (2018)
Limnocharis flava, a problematic weed of rice fields, is reported to have multiple resistance to 2,4-D (synthetic auxin), and bensulfuron-methyl (AHAS inhibitor) due to over-reliance on their use. The present study was conducted to appraise the level of resistance and cross-resistance patterns in L. flava, and to elucidate the mechanisms endowing its resistance. Morphological responses between susceptible (S) and resistant (R) populations were evaluated with a view of addressing the species resistance profile. The levels and patterns of resistance in the R population were determined by LD50 and GR50 values. Seven AHAS inhibitors (bensulfuron-methyl, metsulfuron-methyl, pyrazosulfuron-ethyl, pyribenzoxim, imazethapyr, penoxsulam, and bispyribac-sodium) were examined for their efficacy at different dosages against the S and R populations, respectively. It was found that the S population was successfully controlled by all AHAS inhibitors but the R population survived the applications of the first four from seven tested inhibitors, indicating high-level of resistance to bensulfuron-methyl, with various levels of cross-resistance to other AHAS inhibitors. To demonstrate the mechanisms endowing resistance in the R population, molecular investigation was carried out by AHAS amino acids sequence comparison on R plants that survived the inhibitors application. Evidently, the plants were endowed with similar AHAS gene mutation of single nucleotide polymorphism (SNP) (GAC to GAG). This resulted in Asp substitution by Glu at amino acid position 376, suggesting point mutation as the molecular basis of resistance. In vitro assays were conducted using standards for AHAS inhibitors consisting of bensulfuronmethyl (99.6%), metsulfuron-methyl (99.2%), pyrazosulfuron-ethyl (99.1%), and pyribenzoxim (99.8%) with seven concentrations (0, 0.001, 0.01, 0.1, 1, 10, and 100 μM). The I50 of in vitro AHAS activity showed that R population was >83333-, 398-, 172-, and 48-fold greater than S population for the respective AHAS inhibitors. This suggests stronger cross-resistance to sulfonylureas than to pyrimidinyl (thio) benzoate (pyribenzoxim). The result of non-target site mechanism experiments showed that S and R populations did not differ significantly in their ability to absorb, translocate, and metabolize bensulfuron-methyl. This indicates that non-target site resistance mechanisms of differential metabolism, absorption, and translocation did not confer resistance in the R population. The morphological and physiological characteristics of AHAS inhibitors on S and R populations were examined using progenies of AHAS herbicide-resistant (R) individuals that survived the application of bensulfuron-methyl (Progeny 1) and pyribenzoxim (Progeny 2). Both R and S plants were compared in terms of fresh weight, dry weight, height, epicuticular wax weight, stomata density, leaf area index, and leaf micromorphology for growth assessment. Net photosynthetic rate, stomatal conductance, intercellular carbon dioxide, and transpiration rate were monitored using Progeny 1 from R population with S plants as control. The results showed that R plants carrying AHAS Asp-376-Glu mutation did not differ in the morpho-physiological characteristics and were comparable to that of S plants. In conclusion, the basis of AHAS-inhibitors resistance in L. flava was identified to be due to an Asp-376-Glu mutation that reduced sensitivity of the target site to AHAS inhibitors. The current study presents the first report of resistance mechanism in L. flava.